2003
DOI: 10.1023/b:ejep.0000040529.60673.b7
|View full text |Cite
|
Sign up to set email alerts
|

Three-Year (1999–2002) of Epidemiological and Virological Surveillance of Influenza in North-East Italy

Abstract: The results of the epidemiological and virological surveillance of influenza performed during the 1999/2000, 2000/2001 and 2001/2002 seasons in the northeastern Italy were presented and the relationship between age-specific morbidity rates and circulating strains were discussed.The epidemiological findings pointed out a change in age distribution. During the 1999/2000 season, characterized by a circulation of viruses antigenically close to the vaccine strain, a similar incidence rate in the 0-14 and 15-64-year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Despite the important role of influenza B, much of the published scientific literature regarding the epidemiology of influenza has focused on influenza A, and we still have a relatively poor understanding of global epidemiology and burden of disease of influenza B, especially outside Europe and the United States . Several studies have reported on the burden of disease attributable to influenza B in a single season, or during consecutive seasons in a single country, but only one study thus far has looked at the global epidemiology of influenza B . In particular, it is very important to assess the epidemiology of influenza in the tropics, as this is where approximately 40% of the world's population live, and influenza activity there is quite different from other world regions: countries in the tropics may experience two annual peaks, and epidemics are not as short and intense as in the Northern and Southern hemispheres .…”
Section: Introductionmentioning
confidence: 99%
“…Despite the important role of influenza B, much of the published scientific literature regarding the epidemiology of influenza has focused on influenza A, and we still have a relatively poor understanding of global epidemiology and burden of disease of influenza B, especially outside Europe and the United States . Several studies have reported on the burden of disease attributable to influenza B in a single season, or during consecutive seasons in a single country, but only one study thus far has looked at the global epidemiology of influenza B . In particular, it is very important to assess the epidemiology of influenza in the tropics, as this is where approximately 40% of the world's population live, and influenza activity there is quite different from other world regions: countries in the tropics may experience two annual peaks, and epidemics are not as short and intense as in the Northern and Southern hemispheres .…”
Section: Introductionmentioning
confidence: 99%
“…Background levels in each group were calculated by averaging weekly incidence rates over a six-week period before and after the first and the last virus isolation, respectively. 26 The results of clinical-epidemiological surveillance were published weekly on the CIRI-IV web-site. 23 The results of ILI surveillance performed by the CIRI-IV were aggregated with data from the National Institute of Health (Istituto Superiore di Sanità) in order to construct the global national epidemiological scenario.…”
mentioning
confidence: 99%
“…All the children who received the vaccine were vaccinated before the onset of the influenza season, which was defined as the period including the dates of the first and last isolation of influenza virus as determined by the Italian national surveillance system. The surveillance was performed by means of a computerised network (http://www.influnet.it) that collected clinical reports from 500 sentinel physicians and integrated them with virological surveillance (by the Inter-university Research Centre on Influenza, Department of Health Sciences, University of Genoa, Italy) [13][14][15].…”
Section: Study Population and Vaccine Usementioning
confidence: 99%